Effect of endoscopic ligation combined with traditional Chinese medicine syndrome differentiation-based treatment in the secondary prevention of esophageal variceal bleeding in patients with liver cirrhosis - CHEN Chong (Linchuang Gandanbing Zazhi, 2022)
ObjectiveTo investigate the efficacy of endoscopic ligation combined with traditional Chinese medicine (TCM) syndrome differentiation-based treatment in the secondary prevention of esophageal variceal bleeding (EVB) in patients with liver cirrhosis. Methods A total of 108 EVB patients who were admitted to Department of Liver Cirrhosis, Shuguang Hospital Affiliated to Shanghai University of Traditional Chinese Medicine from April 2015 to February 2021 and underwent endoscopic ligation were enrolled, among whom 59 patients with TCM treatment were enrolled as Chinese and Western medicine group, and 49 patients without TCM treatment were enrolled as Western medicine group. The two groups were compared in terms of the incidence rate of rebleeding, mortality rate, and the improvement rate of portal hypertensive gastropathy. The t-test was used for comparison of normally distributed continuous data between groups, and the Mann-Whitney U rank sum test was used for comparison of non-normally distributed continuous data between groups; the chi-square test or the Fisher’s exact test was used for comparison of categorical data between two groups; a Cox regression analysis was used to evaluate the risk factors for rebleeding. ResultsCompared with the Western medicine group, the Chinese and Western medicine group had a significantly lower rebleeding rate within 13-24 months after ligation (2% vs 12%, P=0.045), a significantly lower mortality rate of rebleeding (2% vs 12%, P=0.045), and a significantly higher overall response rate of portal hypertensive gastropathy (90% vs 77%, P=0.04). Underlying diseases (mainly including diabetes, hypertension, and heart disease) and Child-Pugh class for liver function were significant risk factors for rebleeding (all P＜0.05). ConclusionLigation combined with TCM treatment can significantly reduce the incidence rate of delayed rebleeding and the mortality rate of EVB and improve the degree of portal hypertensive gastropathy, which provides a new strategy for ligation combined with TCM treatment to improve the overall response of EVB secondary prevention.